ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN SUKARELA (VOLUNTARY DISCLOSURE) DALAM LAPORAN TAHUNAN (Studi Empiris Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2013) - Evi Meliana Panjaitan; Kamaliah '; Hariadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The aim of this research is to analyze the factors that influence disclousure extend in annual report in Indonesia. Factors tested in this study are firm size, firm age, leverage, profitability, liquidity and public accounting firm size. Collecting data is using porposive sampling methode to the companies annual reports of consumer goods manufacturing sector listed in Indonesia Stock Exchange for year of 2012-2013. The number of companies taken as samples in this study covers about 60 company annual reports. This research uses multiple regression that use to examine the influence disclousure extend in annual report. The results show that the firm size bring a significant that affect on the extent of voluntary disclosures with significant value 0,002 (alpha 0,05). Firm age on the extent of voluntary disclosures with significant value 0,022. Profitability on the extent of voluntary disclosures with significant value 0,040. Public accounting firm size on the extent of voluntary disclosures with significant value 0,044. However, leverage do not show significant influence on the extent of voluntary disclosures with significant value 0,746 and liquidity do not show significant influence on the extent of voluntary disclosures with significant value 0,273.Keywords: Extensive Voluntary Disclosure, Annual Report and Firm Characteristics